Productive articulation model as a regional innovation system - Ballardo-Cárdenas, Denisse; López-de Alba, Pedro L.; León-Castro, Ernesto; Martínez-Huerta, Ramón (Unidad Editorial UPTC, 2020)
This paper presents a productive articulation model that serves as the basis for developing and enhancing regional innovation systems. The main objective is to generate a process of linkage between the industrial sector, academia, and government within which specific regional problems can be solved through the effective intervention of each of the actors. In addition to the process, a success story is presented from the State of Guanajuato, Mexico, which serves to visualize as a clear and defined process of articulation that allows a transfer of knowledge between the actors. Keywords: Productivity articulation model; regional Innovation system; triple helix. JEL Classification: L38, O18 Received: 30/06/2020. Accepted: 05/11/2020.  Published: 01/12/2020